Nucleic acid aptamers in orthopedic diseases: promising therapeutic agents for bone disorders - Zhenhong He; Qingping Peng; Wenying Bin; Luyao Zhao; Yihuang Chen; Yuanqun Zhang; Weihu Yang; Xingchen Yan; Huan Liu (Bone Research)
Abstract Precision medicine has become a cornerstone in modern therapeutic strategies, with nucleic acid aptamers emerging as pivotal tools due to their unique properties. These oligonucleotide fragments, selected through the Systematic Evolution of Ligands by Exponential Enrichment process, exhibit high affinity and specificity toward their targets, such as DNA, RNA, proteins, and other biomolecules. Nucleic acid aptamers offer significant advantages over traditional therapeutic agents, including superior biological stability, minimal immunogenicity, and the capacity for universal chemical modifications that enhance their in vivo performance and targeting precision. In the realm of osseous tissue repair and regeneration, a complex physiological process essential for maintaining skeletal integrity, aptamers have shown remarkable potential in influencing molecular pathways crucial for bone regeneration, promoting osteogenic differentiation and supporting osteoblast survival. By engineering aptamers to regulate inflammatory responses and facilitate the proliferation and differentiation of fibroblasts, these oligonucleotides can be integrated into advanced drug delivery systems, significantly improving bone repair efficacy while minimizing adverse effects. Aptamer-mediated strategies, including the use of siRNA and miRNA mimics or inhibitors, have shown efficacy in enhancing bone mass and microstructure. These approaches hold transformative potential for treating a range of orthopedic conditions like osteoporosis, osteosarcoma, and osteoarthritis. This review synthesizes the molecular mechanisms and biological roles of aptamers in orthopedic diseases, emphasizing their potential to drive innovative and effective therapeutic interventions.